Epidemiological characterization of exogenous poisoning cases in the state of Pará between 2012 and 2021 - Batista Neto, José Benedito dos Santos; Castro, Thiago Marcírio Gonçalves de; Silva, Herberth Rick dos Santos; Almeida, Cristielle Larissa Sousa de; Cantão, Benedito do Carmo Gomes; Silva Filho, José Adelmo da; Borba-Pinheiro, Claudio Joaquim (Revista de Enfermagem da UFPI, 2023)
Objective: To characterize the epidemiological profile of exogenous poisoning cases in the state of Pará between 2012 and 2021. Methods: Quantitative, descriptive and cross-sectional study, based on data collected from the Notifiable Diseases Information System. Results: During this period, 5,803 cases of exogenous poisoning were recorded in Pará. There was a predominance of females (56.92%), aged between 20 and 39 (39.10%) and brown (74.93%). The circumstances that stood out were suicide attempts (32.62%) and accidental use (24.47%), the toxic agents drugs (25.52%) and agricultural pesticides (13.42%), cases of acute-single exposure (58.94%), clinical diagnosis (47.11%) as a confirmation criterion and progression to cure without sequelae (65.88%). When relating circumstances to age group and gender, a high number of suicide attempts were identified among young people and adults (n=1,633), mainly women (n=1,198), while in accidental use, the main victims were children (n=840), especially males (n=740). Conclusion: Exogenous poisoning has become a health problem in the state of Pará, with specific characteristics, and it is necessary to promote health education to help alert children, young people, families and the community as a whole.